Acuidade visual, sensibilidade ao contraste, acuidade estereoscópica: estudo de caso controle em escolares com baixo peso ao nascer - Ferrari, Maria Valeria [UNIFESP] (2016)
Low birth weight (LBW) is one of the most important risk factors for neonatal mortality in addition to being one of the determinants of morbidity in childhood. The emergence of new technologies has provided a high survival rate in this group of infants with low birth weight, however, does not prevent the onset of sequelae that can lead to damage to neurodevelopment. Prematurity and congenital infections as well as intrauterine growth restriction are some factors related to LBW that can lead to intellectual, auditory and visual deficits. Objective: To evaluate the visual functions of visual acuity, contrast sensitivity and stereopsis tests of schoolchildren with low birth weight comparing them to school adequate weight and to analyze the association of visual changes to birth weight, gestational age and Apgar. Methods: Cross-sectional study of the case-control carried out in 520 children at 6 to 10 years old in the municipal Embu das Artes - SP - from August 2011 to March 2012. Results: We found that there was no difference statistically significant between the groups in the functions analyzed in relation to birth weight and Apgar, but in relation to gestational age there was poor results in visual acuity (P = 0.016) and stereo acuity (p = 0.006) in preterm school the which did not occur in the contrast sensitivity function (p = 0.636). Conclusions: Low birth weight is a risk factor for changes in visual functions although limited relevance, underscoring the need for more targeted attention to those students born with small gestational age caused by the marked immaturity of the visual system.